Auranofin prevents liver fibrosis by system Xc-mediated inhibition of NLRP3 inflammasome - Hyun Young Kim (Nature Portfolio, 2021)
Using mouse models of liver fibrosis, Kim et al examined the mechanisms underlying the antifibrotic inhibition of the NLRP3 inflammasome by auranofin. They demonstrated that auranofin-induced inhibition of the NLRP3 inflammasome in bone marrow-derived macrophages and kupffer cells was mediated via inhibition of the cystine-glutamate antiporter, system Xc, which advances our understanding of the mechanism by which auranofin exerts its therapeutic effects.